2008
DOI: 10.1016/j.rmed.2008.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor attendance at an outpatient pulmonary rehabilitation programme

Abstract: Attendance at PRPs is independently influenced by smoking status, the degree of breathlessness, frequency of hospital admissions, length of the programme and journey time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
112
5
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 11 publications
(22 reference statements)
15
112
5
7
Order By: Relevance
“…In this study, the anxiety and depression scores of the patients completing the PR program were higher, and there was no statistically significant difference between the two groups. Smoking was also an important factor affecting the adaptation and attendance in PR programs (3,4,17,21,25). In this study, patients reported that active cigarette use was a reason for not attending the programs (6%).…”
Section: Discussionmentioning
confidence: 69%
“…In this study, the anxiety and depression scores of the patients completing the PR program were higher, and there was no statistically significant difference between the two groups. Smoking was also an important factor affecting the adaptation and attendance in PR programs (3,4,17,21,25). In this study, patients reported that active cigarette use was a reason for not attending the programs (6%).…”
Section: Discussionmentioning
confidence: 69%
“…Despite its many proven effects, it was reported in the literature that the rate of participation in PR fell to 50% and the discontinuation rate was 23-31% (8)(9)(10). In the studies conducted, transportation, work conditions, a level of increased shortness of breath, and low social support were observed to be among the reasons for noncompliance and nonattendance in PR programs (8,9,(11)(12)(13). Those who have transportation and work problems or a high level of perception of shortness of breath as well as advanced-stage and bedbound cases also benefit from PR by means of supervised home-based, remotely supervised, and unsupervised programs.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously reported that a longer PRP was associated with lower attendance 10 . Possible reasons could be that participants notice less incremental change and that there is more time for intercurrent illness/exacerbations or other activities to interfere with attendance.…”
mentioning
confidence: 84%
“…However, there still remain unanswered questions including what are the best sites for delivery of a PRP, whether nutritional supplementation should be offered during PRP, what are optimal target populations and what post-rehabilitation maintenance strategies reduce the declines seen in nearly all settings [7][8][9] . Other important concerns relate to variable attendance and high drop-out rates in PRPs 10,11 . We have shown that certain factors at enrolment can predict later poor attendance at PRP 10 , but interventions to improve the completion rates of these more vulnerable groups are still being researched.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation